2020
DOI: 10.1038/s41598-019-57133-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of between-group differentiation in male kinship between bonobos and chimpanzees

Abstract: Patterns of kinship among individuals in different groups have been rarely examined in animals. Two closest living relatives of humans, bonobos and chimpanzees share many characteristics of social systems including male philopatry, whereas one major difference between the two species is the nature of intergroup relationship. Intergroup relationship is basically antagonistic and males sometimes kill individuals of other groups in chimpanzees, whereas it is much more moderate in bonobos and copulations between i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…This hypothesis is supported by our previous finding that bonobos were less likely to terminate associations when ranging in less familiar areas of their home range (Lucchesi et al 2020). On the social level, the fact that communities were less likely to terminate associations when the number of maximally tumescent females in the party was high indicates the possibility of reproductive advantages to these associations (but see Ishizuka et al 2018Ishizuka et al , 2020.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…This hypothesis is supported by our previous finding that bonobos were less likely to terminate associations when ranging in less familiar areas of their home range (Lucchesi et al 2020). On the social level, the fact that communities were less likely to terminate associations when the number of maximally tumescent females in the party was high indicates the possibility of reproductive advantages to these associations (but see Ishizuka et al 2018Ishizuka et al , 2020.…”
Section: Introductionmentioning
confidence: 52%
“…In many species, members of different groups associate with the purpose to increase the number of social (African elephants, L. africana: Wittemyer et al 2005) and mating (Hanuman langurs, S. entellus: Launhardt et al 2001;Verreaux's sifaka, P. verreauxi: Lawler 2007) partners or to evaluate the possibility of transfer from their natal group (meerkats, S. suricatta: Drewe et al 2009). In bonobos, non-energetic benefits of associations may include extra-community paternities (but see Ishizuka et al 2018;Ishizuka et al 2020), facilitation of the transfer of young nulliparous females or even males to other communities (Hohmann 2001;Sakamaki et al 2015;Toda et al 2018), and maintenance of social bonds among females of adjacent communities (Sakamaki et al 2018). For instance, copulation between members of different communities is common during associations (Furuichi 2011;Lucchesi et al 2020), and in previous research we have shown that communities are more likely to remain in association when the number of maximally tumescent females is high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating and understanding behavioural interactions among individuals, patterns of mate selection (Vigilant et al, 2001), dispersal and intergroup migration (Cheney & Seyfarth, 1983; Langergraber et al, 2014; Van Cise et al, 2017), group fission and critical aspects of natural selection such as variation in interbirth intervals or infant survivorship (Silk et al, 2003) requires information about the relationships among the actors in the continual drama of mammalian social behaviour and life history. Unfortunately, documenting kinship among individuals in natural populations of animals, especially among long‐lived mammals such as primates, cetaceans, elephants and other large‐bodied species, has traditionally required many years (often decades) of continuous observation of recognizable individuals (Alberts & Altmann, 2012; Ishizuka et al, 2020; McComb et al, 2001). Even then, paternity is often uncertain without some form of genetic testing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, investigations of smaller animals with shorter generation times but that are migratory or are otherwise difficult to repeatedly observe or identify can also present challenges for the assessment of kinship among study individuals. Research in various aspects of the ethology, social organization, ecology, demography and population genetics of natural populations benefits directly from methods to identify or confirm relationships among individuals that do not require long‐term observation of habituated populations (Foroughirad et al, 2019; Ishizuka et al, 2020; Langergraber et al, 2014; Snyder‐Mackler et al, 2016; Stadele et al, 2016; Van Cise et al, 2017). In addition, biomedical research using captive populations of nonhuman primates or other species can benefit from the capacity to determine parentage or other relationships among individuals whenever reliable pedigree information is not available (Kanthaswamy et al, 2006; Rogers et al, 2006; Vinson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%